2019
DOI: 10.11648/j.urp.20190401.11
|View full text |Cite
|
Sign up to set email alerts
|

Urban Growth Evaluation by Coupling Descriptive Analysis and Zipf’s Rank-Size Model in Parakou (Benin)

Abstract: Parakou occupies a strategic place in the socio-economic development of Benin due to its geographical position.Based on the Urban Land Registry data, and census data from the National Institute of Statistics and Applied Economics coupling with the statistical description and adjustment to the distribution Zipf rank-size model, allowed us to describe the urban hierarchy on the scale of Parakou localities over the period 1979 to 2013. The changes in densities of population occupation per decade show a tendency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
1
0
3
Order By: Relevance
“…La mise en oeuvre de la foresterie urbaine procure de nombreux bénéfices à la population (Lanmandjèkpogni et al, 2019 ;Tzoulas et al, 2007). Les forêts urbaines sont des éléments importants des paysages urbains.…”
Section: Perception Des Résidents Sur L'état De La Végétation De Leur...unclassified
See 2 more Smart Citations
“…La mise en oeuvre de la foresterie urbaine procure de nombreux bénéfices à la population (Lanmandjèkpogni et al, 2019 ;Tzoulas et al, 2007). Les forêts urbaines sont des éléments importants des paysages urbains.…”
Section: Perception Des Résidents Sur L'état De La Végétation De Leur...unclassified
“…La croissance démographique de nombreuses villes africaines, et la non-maîtrise de l'aménagement des zones loties et habitées ont progressivement réduit la place et le rôle de la végétation dans les municipalités en plein essor (Bawa, 2017). D'une part, la forte demande d'espace pour les infrastructures humaines est souvent satisfaite au détriment de la végétation naturelle et des espaces verts (Lanmandjèkpogni et al, 2019 ;Folega et al, 2019). D'autre part, il est un constat que le verdissement de la ville, la protection de la biodiversité et la promotion des espèces de la flore locale (à travers les espaces publics verts, haies vives, forêts urbaines et périurbaines, parcs urbains) sont peu promus, dans de nombreuses villes africaines (FAO, 2009).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…For example, Deng et al [25] explored China's urban built-up area with Zipf's law to explain that the built-up areas of all cities in China had maintained a growth trend, but the rate of expansion varies greatly from period to period. Census data from the National Institute of Statistics were combined with the population and GDP to estimate the Zipf's index [26][27][28][29]. Previously, Wen et al [30] showed that China's urban scale distribution was relatively balanced, virtually conforming to Zipf's law by using China's urban population data from 1990 to 2010 and a double-logarithmic regression model to test China's urban scale and urban rank through Zipf's law.…”
Section: Introductionmentioning
confidence: 99%